KUKER (Curricular, Co-Curricular, And Extracurricular) Based Integrated Learning Model Development In Strengthening The Competitiveness And Independence - Amri, Syaiful; Rachman, Dedy Febry; Wardani, Rosyia; Helmida, Baiq Ertin (LPPM Institut Pendidikan Nusantara Global, 2025)
This study is to create an Integrated Learning Model Based on KUKER (Curricular, Co-curricular, Extracurricular) to improve the competitiveness and independence of AMM Mataram School of Economics graduates. The research method adapts the Borg & Gall model, which comprises problem identification, expert validation, limited trials, and qualitative and quantitative data analysis, using a mixed-method design (qualitative-quantitative) and a Research and Development (R&D) approach. Qualitative analysis findings reveal a rise in holistic integration among learning components, simplicity of structure, and digital-based innovations. While 100% of students said strong agreement on the gain in job preparedness, soft skills, and independence, expert validation showed a rise in the average score from 2.57 (fair) to 4.0 (very good). Therefore, this study demonstrates the KUKER model's efficacy and viability for use.